Public and private economic and legal interests in the field of international transport in the latest edition of Incoterms - Матвєєв, Петро Сергійович; Матвєєв, П. С.; Матвеев, Петр Сергеевич; Matvieiev, Petro S.; Клепікова, Ольга Вікторівна; Клепікова, О. В.; Клепикова, Ольга Викторовна; Klepikova, Olha V.; Klepikova, Olga; Корнута, Людмила Михайлівна; Корнута, Л. М.; Корнута, Людмила Михайловна; et al. (Editorial Primmate S. A. S., 2021)
The article examines the importance of maintaining a balance of public and private interests when using "autonomy of will" in international trade. The relevance of this study is because the field of international transport is dynamic (closely related to the economy), the sphere of public activity that requires constant monitoring and updating. Purpose: to investigate the process of implementation of economic and legal tasks in the field of international transportation, taking into account the entry into force of the new version of the Code of Trade Rules - Incoterms. Methodology: logical-semantic, historical, analytical, comparative analysis, and synthesis. Research results: such foreign economic activity as international transportation is considered, the basic conditions of Incoterms 2020 terms concerning international transportations and conditions of realization by contractors of the economic-legal interests through observance of these conditions are allocated and analyzed in detail. The work can be used in preparation for the conclusion of a foreign trade agreement.

У статті аналізується важливість дотримання балансу публічних та приватних інтересів під час використання "автономія волі" в сфері міжнародної торгівлі. Актуальність цього дослідження обумовлена тим, що сфера міжнародних перевезень це динамічна (тісно пов'язана з економікою), сфера громадської діяльності, яка потребує постійного моніторингу та оновлення. Мета роботи: дослідити процес реалізації економіко-правових завдань у галузі міжнародних перевезень з урахуванням набрання чинності новою редакцією зведення торгових правил – Інкотермс. Методологія роботи: логіко-семантичний, історичний, аналітичний, порівняльний аналіз, та синтез. Результати дослідження: розглянуто такий зовнішньоекономічний вид діяльності, як міжнародні перевезення, виділено та детально проаналізовано базові умови термінів Інкотермс 2020, які стосуються міжнародних перевезень та умови реалізації контрагентами своїх економіко-правових інтересів за допомогою дотримання цих умов. Робота може бути використана в процесі підготовки до укладання зовнішньоекономічної угоди.
Matvieiev P. Public and private economic and legal interests in the field of international transport in the latest edition of Incoterms / P. Matvieiev, O. Klepikova, L. Kornuta, M. Abbaszade, S. Kuznetsov // Amazonia Investiga. – Vol. 10. - Issue 46. – Editorial Primmate S. A. S., 2021. – P. 217-224.
Keywords: international transportation; international trade; legal regulation; Incoterms; міжнародні перевезення; міжнародна торгівля; правове регулювання; Інкотермс; Research Subject Categories::LAW/JURISPRUDENCE